Production and characterisation of monoclonal antibodies against RAI3 and its expression in human breast cancer - Kiefer Hans; Di Fiore Stefano; ten Haaf Anette; Hartmann Arndt; Dahl Edgar; Bektas Nuran; Jörißen Hannah; Thess Andreas; Barth Stefan; Klockenbring Torsten (BMC Cancer, 2009)
Abstract Background RAI3 is an orphan G-protein coupled receptor (GPCR) that has been associated with malignancy and may play a role in the proliferation of breast cancer cells. Although its exact function in normal and malignant cells remains unclear and evidence supporting its role in oncogenesis is controversial, its abundant expression on the surface of cancer cells would make it an interesting target for the development of antibody-based therapeutics. To investigate the link with cancer and provide more evidence for its role, we carried out a systematic analysis of RAI3 expression in a large set of human breast cancer specimens. Methods We expressed recombinant human RAI3 in bacteria and reconstituted the purified protein in liposomes to raise monoclonal antibodies using classical hybridoma techniques. The specific binding activity of the antibodies was confirmed by enzyme-linked immunosorbent assay (ELISA), western blot and immunocytochemistry. We carried out a systematic immunohistochemical analysis of RAI3 expression in human invasive breast carcinomas (n = 147) and normal breast tissues (n = 44) using a tissue microarray. In addition, a cDNA dot blot hybridisation assay was used to investigate a set of matched normal and cancerous breast tissue specimens (n = 50) as well as lymph node metastases (n = 3) for RAI3 mRNA expression. Results The anti-RAI3 monoclonal antibodies bound to recombinant human RAI3 protein with high specificity and affinity, as shown by ELISA, western blot and ICC. The cDNA dot blot and immunohistochemical experiments showed that both RAI3 mRNA and RAI3 protein were abundantly expressed in human breast carcinoma. However, there was no association between RAI3 protein expression and prognosis based on overall and recurrence-free survival. Conclusion We have generated a novel, highly-specific monoclonal antibody that detects RAI3 in formaldehyde-fixed paraffin-embedded tissue. This is the first study to report a systematic analysis of RAI3 expression in normal and cancerous human breast tissue at both the mRNA and protein levels.